PENGARUH PENERAPAN METODE FERNALD TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Ely Alfina; Daviq Chairilsyah; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations in the ability to read the beginning of the students have not developed optimally. So it is necessary to use the method/media of the Fernald method. The purpose of this study is to examine the influence of application of the Fernald method on the starting ability to read children aged 5-6 years. This research was conducted at TK Negeri Pembina 1 Pekanbaru from March 2019 until October 2019 for observation and research. Research using experimental methods with the design of one group pre-Test post-Test design with a sample number of 20 children. The data collection techniques used in this research are using the observation sheet of the child's initial reading ability. The data analysis technique uses the T-test test using the SPSS ver 20 program. From the results of data analysis obtained Thitung amounted-21.002 greater than this = 2.039 with sig 0.000 < 0.05. It can be concluded that there is a significant difference in children's initial reading ability before and after the use of the Fernald method. Based on the hypothesis test results acquired there was influence of the use of the Fernald method to the ability to read the beginning of children aged 5-6 years KINDERGARTEN State Pembina 1 Pekanbaru amounted to 50.47%.Key Words : Fernald's Method, Initial Reading Ability